A Longitudinal Study of Motivation and Goal Difficulty on Goal Progress and Mental Contrasting with Implementation Intentions (MCII). - Lombard, Merrill (Curtin University, 2024)
This study investigated longitudinal impact of autonomous motivation and controlled motivation on goal progress at both between- and within-person levels. Additionally, it examined whether MCII, a metacognitive strategy, would moderate associations between controlled motivation and goal-related outcomes, and explored potential relationships between goal motives and within-person variability in goal-related outcomes. Individuals reported more within-person variability in goal progress and less variability in time spent on goal pursuit when they had stronger controlled motivation.